Analisis Pendistribusian Yang Efektif Guna Meningkatkan Penjualan Produk Indofood di PT Alam Jaya - Sierna Ndruru; Aferiaman Telambanua; Otanius Laia; Perlindungan F. Hulu (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effectiveness of Indofood product distribution in increasing sales at PT. Alam Jaya Kota Gunungsitoli and to identify the factors influencing this effectiveness. Effective product distribution is crucial in achieving sales targets and maintaining market position. This research analyzes how the distribution system implemented by PT. Alam Jaya contributes to the increased sales of Indofood products. The results show that the distribution of Indofood products by PT. Alam Jaya Kota Gunungsitoli has positively impacted sales growth. A well-organized distribution system, including wide regional coverage, timely delivery, and product availability at various sales points, are key factors supporting the sales increase. Additionally, strong collaboration between distributors and retailers plays a vital role in ensuring the consistent availability of products in the market. Other factors influencing distribution effectiveness include the company's ability to manage stock optimally, effective marketing strategies, and adaptation to local market conditions. This study illustrates that a well-planned and structured distribution can be an effective tool in supporting the sales growth of Indofood products at PT. Alam Jaya Kota Gunungsitoli.